Two-Dimensional Coupled Solution for Thermoelastic Beams via Generalized Dual-Phase-Lags Model. Issue 3 (3rd May 2016) - Zenkour, Ashraf M.
Abstract: The generalized thermoelastic problem of a thick-walled simply-supported beam subjected to different applied heat source and mechanical loads at its surfaces is studied. The thermoelastic coupling differential equations of motion of the beam are established. The generalized thermoelasticity based on the dual-phase-lags (DPLs) theory is considered to treat this problem. An exact 2-D coupled solution is presented to deduce analytical expressions for the temperature, displacements and stresses. The time-harmonic motion behavior as well as the thermal and mechanical conditions at the bounded faces of the beam is used for this purpose. The effect of the DPLs on the field quantities against the axial and normal directions of the beam under thermomechanical loads is discussed. Final investigations to various thermoelastic models are made.